BAGI HASIL PENGAMBILAN AIR NIRA DALAM TINJUAN FIQH MUAMALAH (Studi di Jorong Koto Dalimo Nagari Supayang) - Riri Syafitri; Farida Arianti (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This study examines the implementation of profit sharing in cooperation to extract sap water in Jorong Koto Dalimo Nagari Agarng which is close to the Musaqah (agricultural cooperation) contract in the form of managing sap water into palm sugar. The agreed terms of profit sharing are that within seven days of sap-water extraction, six days of sap-water extraction are for the manager and one day for the sap tree owner. the agreed profit sharing is in the form of palm sugar. The problem is that there is a disproportionate pattern of profit sharing between the owner of the sap tree and the manager of the sap water, the profit sharing is more dominant to the manager. This research uses field research. The data were obtained through interviews and observations, and then the data were narrated descriptively. The result achieved is that the implementation of cooperation in extracting sap water with a profit sharing agreement of 6:1 is punished proportionally and is allowed in Islam because it has fulfilled the principle of justice in sharing the results.